Eco-friendly biosurfactant solutions for petroleum hydrocarbon cleanup in aquatic ecosystems - Sumitha Elayaperumal; Yuvaraj Sivamani; Debasmita Bhattacharya; Dibyajit Lahiri; Moupriya Nag (Sustainable Chemistry for the Environment)
Hydrophobic compounds that offer C-H bonds along with heavy metals such as lead, mercury, and cadmium residing in terrestrial and aquatic environments are very much harmfully threatening to the health of an ecosystem. Petroleum-derived hydrocarbons such as fuels (gasoline, diesel etc.), LPG, waxes, etc. are, in fact, one of the most poisonous and carcinogenic contaminants out of all hydrocarbons, caused and acquired through petroleum. They are carcinogenic, neurotoxic and can cause damage to respiratory system, skeletal system along with damaging other organs. These are very stable in the environment and become concentrated and magnified in the tissues of living organisms and, therefore, increased in their ecological effects. Bioremediation has emerged as a viable option; however, it enhances the effectiveness of biosurfactant such as surfactin which is an amphiphilic, bacterially derived surface-active compound that can be utilized in the present work. Such surfactants can increase a pollutant's surface area for contact, create microenvironments, and emulsify media for pollutant removal. There are several recent approaches using biosurfactants in the environment where they improve bioaccessibility of hydrophobics, remove toxic heavy metals, and accelerated the biodegradation process. They are expected to extract any heavy metal from soils by anionic nature and capacity to bind with metal ions. In addition, the best in-situ remediation using biosurfactant-producing microorganisms can also become an efficient and cost-effective method for cleaning crude oil and petrochemical contaminants from water. This article describes how biosurfactants such as surfactin, rhamnolipid etc. can be beneficial to the process of environmental restoration in terms of modelling sustainable approaches of rehabilitating contaminated sites. Biosurfactants can advance remediation technologies through their unique properties and help in creating a cleaner, healthier ecosystem.